Tehnične lastnosti vozičkov na elektromotorni pogon za zelo težko gibalno oviranost, predpisanih v letih 2008 in 2017 - Moharić, Metka (Rehabilitacija (Ljubljana), 2019)
Introduction: In 2007, methods and procedures for prescribing and testing of tertiary-level wheelchairs were published. Since then, only a few minor corrections have been made. The aim of the study was to find out whether the technical characteristics of the prescribed powered wheelchairs for patients with very severe movement impairments in years of 2008 and 2017 differed; we also tried to determine the reasons for the changes. Methods: We searched through the copies of the test sheets for powered wheelchairs for very severe movement impairment, which were prescribed at the University Rehabilitation Institute, Republic of Slovenia, in the years 2008 and 2017. In doing so, we focused on technical features that improve the user's independence and thus his/her quality of life. Results: In 2007, we prescribed 49 powered wheelchairs for very severe movement impairment, in 2017 we prescribed 91 of them. Few wheelchairs had additional functions in 2007, while in 2017, 72.5 % of wheelchairs with additional functions were prescribed. Among them, power elevating seat and power foot rest elevation were the most frequently prescribed additional features. Conclusion: Technological advances and changes in the payment process of wheelchairs allow us to prescribe several additional wheelchair technical features. As a result, the officially published methods and procedures for prescribing wheelchairs no longer fit, therefore substantial changes are needed.
Keywords: gibalna oviranost; invalidski vozički; medical aids; medicinski pripomočki; movement impairment; predpisovanje; prescription; terciarno zdravstvo; tertiary health care; Wheelchairs